The Royal Navy in the Falklands Conflict and the Gulf War : culture and strategy - Finlan, Alastair (British politics and society., 2004)
This book provides an insight into the relationship betweeen the Royal Navy's institutional culture and modern warfare with specific reference to the Falklands Conflict and the Gulf War.